Use of the Oxygen Radical Absorbance Capacity (Orac) Assay to Predict the Capacity of Mango (Mangifera Indica L.) By-Products to Inhibit Meat Protein Oxidation - Lissi-Gervaso, E (Springer New York LLC, 2017)
The potential activity of mango by-products to inhibit the peroxyl radical-mediated oxidation of tryptophan residues (Trp) of myofibrillar proteins (MP) was studied. Extracts of seeds, peels and pulps were studied in terms of their antioxidant activity, assessed by the oxygen radical absorbance capacity (ORAC) assay employing fluorescein and pyrogallol red as probes (ORAC-FL and ORAC-PGR, respectively). The effect of the extracts of mango by-products on the oxidation of Trp was evaluated by fluorescence spectroscopy. Data obtained employing the ORAC-FL assay showed a low discrimination of the antioxidant activity of the samples (Peel ≈ Seed > Pulp). However, employing the ORAC-PGR assay it was possible to differentiate the antioxidant activity of the samples (Seed > Peel >> Pulp). Extracts obtained from mango seed, peel, and pulp protected Trp of MP when the latter was exposed to AAPH (2,2′-azo-bis(2-amidinopropane) dihydrochloride)-derived free radicals. Such effect was in good agreement with the ORAC-PGR data, showing that this assay could be employed to predict the protection of Trp residues of MP. © 2016, Springer Science+Business Media New York.